#### Question

Solve the following quadratic equations by factorization:

a(x^{2} + 1) - x(a^{2} + 1) = 0

#### Solution

We have been given

a(x^{2} + 1) - x(a^{2} + 1) = 0

ax^{2} - (a^{2} + 1)x + a = 0

ax^{2} - a^{2}x - x + a = 0

ax(x - a) - 1(x - a) = 0

(ax - 1)(x - a) = 0

Therefore,

ax - 1 = 0

ax = 1

x = 1/a

or,

x - a = 0

x = a

Hence, x = 1/a or x = a

Is there an error in this question or solution?

#### APPEARS IN

Solution Solve the Following Quadratic Equations by Factorization: A(X2 + 1) - X(A2 + 1) = 0 Concept: Solutions of Quadratic Equations by Factorization.